External invasive resorption: Possible coexisting factors and demographic and clinical characteristics. (20th August 2018) - Shemesh, Avi; Levin, Avi; Ben Itzhak, Joe; Brosh, Yair; Braverman, Evgeny; Batashvili, Gabriel; Solomonov, Michael
Abstract: The purpose of this retrospective study was to identify the coexisting factors for EIR and to characterise EIR clinically and demographically. All cases of EIR that were referred to the endodontic department between 2011 to 2016 and diagnosed by an endodontist were evaluated. Demographic and clinical characteristics were collected and evaluated. Thirty‐eight cases of EIR diagnosed between 2011 and 2016 were included in the study. Seventy‐one percent of EIR cases were misdiagnosed by general practitioners. The most affected teeth were the maxillary central incisors (29% of cases) and mandibular molars (26%). Sixty‐eight percent of EIR cases were diagnosed in teeth with clinically normal pulp. Pulp necrosis was observed mainly in the advanced stages (class 3 and class 4) of EIR (75%) and in teeth with a history of trauma (63%). Histories of previous trauma and orthodontic treatment were reported in 29% and 23% of cases, respectively.